2018
DOI: 10.1111/apha.13211
|View full text |Cite
|
Sign up to set email alerts
|

The novel antidepressant ketamine enhances dentate gyrus proliferation with no effects on synaptic plasticity or hippocampal function in depressive‐like rats

Abstract: Aim:Major depressive disorder is a common and debilitating condition with substantial economic impact. Treatment options, although effective, are aimed at relieving the symptoms with limited disease modification. Ketamine, a commonly used anaesthetic, has received substantial attention as it shows rapid antidepressant effects clinically. We studied the effects of ketamine on hippocampal function and dentate gyrus proliferation in rats showing a depressive-like phenotype. Methods: Adolescent and adult animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…In contrast, Choi et al (2016) reported that ketamine fails to enhance cell differentiation or maturation into neurons, although ketamine accelerates cell proliferation in the DG. Moreover, Michaelsson et al (2019) reported that ketamine increases the DG proliferation and exerts no effect on synaptic efficacy or induction of long-term potentiation in both dorsal and ventral hippocampus. Together these studies indicate that neurogenesis could be involved in the sustained but not rapid actdions of ketamine, although additional studies needed to further examine this question.…”
Section: Role Of Neurotrophic Factors In the Rapid Antidepressant Actions Of Ketaminementioning
confidence: 99%
“…In contrast, Choi et al (2016) reported that ketamine fails to enhance cell differentiation or maturation into neurons, although ketamine accelerates cell proliferation in the DG. Moreover, Michaelsson et al (2019) reported that ketamine increases the DG proliferation and exerts no effect on synaptic efficacy or induction of long-term potentiation in both dorsal and ventral hippocampus. Together these studies indicate that neurogenesis could be involved in the sustained but not rapid actdions of ketamine, although additional studies needed to further examine this question.…”
Section: Role Of Neurotrophic Factors In the Rapid Antidepressant Actions Of Ketaminementioning
confidence: 99%
“…[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]121 There is some evidence for the modifying effects of ketamine on epigenetic processes present in BD, [64][65][66][67][68][69][70] as well as its ability to regulate inflammation. [62][63][64][65][66][67][68][69] Ketamine may also have favorable effects on gut microbiota, which have been shown to be disturbed in patients with BD. [71][72][73][74][75][76][77][78] The majority of the above-mentioned effects, however, are based on preliminary evidence and engage unipolar depression model, and therefore require confirmation by studies in bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“… 61 However, some studies have shown contrary evidence and do not support the beneficial effect of ketamine on synaptic plasticity and the proliferation of neurons in rats. 62 , 63 Taken together, it is likely that neurogenesis could have a role in the sustained actions of ketamine; nevertheless, this remains to be confirmed by future studies.…”
Section: Ketamine In Bipolar Disorder – Molecular Datamentioning
confidence: 98%
“…Ketamine inhibited the activity of macrophages and the production of pro-inflammatory cytokines ( Chang et al, 2016 ). Pain and surgery-related psychological stress induce harmful neurobiological effects on immature brain, which is related to brain development damage and long-term behavioral consequences ( Brummelte et al, 2012 ; Michaelsson et al, 2019 ). Ketamine can reduce neuronal activation and cell death in cortex and subcortical area of neonatal rats caused by inflammatory pain ( Liu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%